Border and behind-the-border restrictions in logistics and trade facilitation in the Philippines some results of regulatory dialogues - Llanto, Gilberto M.; Navarro, Adoracion M.; Ortiz, Ma. Kristina; Detros, Keith C. (2013)
The Philippines` potential to capitalize on the gains of regional economic integration depends on its resolve to address the reform gaps and challenges that undermine the efficient and effective regulation and management of trade facilitation at the border and behind the border.

This Policy Note summarizes the findings of the Philippine research team in a study funded by the Economic Research Institute for ASEAN and East Asia that probed the regulatory environment and the remaining border and behind-the-border restrictions in logistics and trade facilitation in the region. The study also covered customs services as these are the forefront services in trade facilitation. Based on the findings, the research team formulated some policy recommendations intended to guide the way forward.
Keywords: Free trade; Commerce; Foreign trade regulation